A Study on Non-Meat Eating and Compassion based on Buddhist Cognition - Zhang, Dr.Jingting; Li, Minxin (Journal of Dhamma for Life, 2023)
Both of Theravada and Vajrayana Buddhism allow meat eating, only Mahayana Buddhism follow the precept of non-meat eating, how does it connect with compassion that emphasized in Mahayana Buddhist practice, and has any conflicts with Theravada Buddhism? The Findings show that Theravada Buddhism does not follow the precept of non-meat eating, because it created no obstacles in attaining the goal of Nibbāna if the non-killing precept is not broken. On the other hand, monks cannot be choosy about food when they are going for alms. Mahayana Buddhism emphasizes non-meat eating because of the practice of Bodhisattva aiming to cultivate compassionate heart. Whether or not to eat meat does not conflict with different goals of Theravada and Mahayana: Nibbāna and Buddhahood.